THE MEDIATING EFFECT OF ATTITUDES TOWARD SCIENCE IN THE PERCEPTIONS OF SCIENCE CLASSROOM ENVIRONMENT, FAMILY INVOLVEMENT, AND SCIENCE SELF-EFFICACY WITH SCIENCE ACHIEVEMENT - CANDIA, LEONA A; Fah, Lay Yoon (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2024)
Previous research has indicated that attitudes influence various factors contributing to scientific achievement. Inadequate performance in science can limit career opportunities, underscoring the importance of comprehending how attitudes towards science can enhance overall scientific achievement. This study explored the mediating effect of attitudes towards science for the relationships between perceptions of science classroom environment, family involvement, and science self-efficacy with science achievement. This research was conducted as a non-experimental quantitative research. Questionnaires from modified established instruments, Test of science-Related Attitudes, What Is Happening In this Class, Family Involvement Questionnaire- High School Version, Sources of science Self-Efficacy, and science Achievement Test, were sent out to participants via Google Form in different days for a span of two weeks. A total of 148 Form 2 upper-secondary school students from various districts in Sabah participated in this study. Data were analyzed using the Partial Least Squares Structural Equation Modeling method. The results revealed that Social Implications of science had a significant positive mediating effect between perceptions of science classroom environment and science achievement. Additionally, there was no significant mediating effect of attitudes toward science on the relationship between science self-efficacy, and family involvement with science achievement. Overall, this study suggests that an aspect of attitudes toward science, the Social Implications of science, was an important mediator between students’ perceptions of science classroom environment and science achievement. This meant that students would perform better in science when they perceived their science classroom better, in the condition that they value the implications that science brings to real life.